Peningkatan Hasil Belajar Peserta Didik Dengan Model Pembelajaran Scramble Dalam Pokok Bahasan Mengasihi dan Menghasilkan Perubahan Pada Mata Pelajaran Pendidikan Agama Kristen - Sertiana Siahaan (PIJAR: Jurnal Pendidikan dan Pengajaran, 2022)
The objectives of this research are 1) to find out whether there is a significant influence with the Scramble learning model. 2) To improve students' cognitive abilities on the subject of Loving and Generating Change. This research is using qualitative with the type of Classroom Action Research (CAR) conducted at SMA Negeri 5 Pematangsiantar which is located at Jalan. Medan Km. 6,8, Ex. Tanjung Tongah, Kec. Siantar Martoba, Pematangsiantar. The subjects of this study were students of class X PMIA 1 and X PMIA 2 with a total of 28 students. The data collection techniques used are tests and observations. There are four stages of the procedure in this study, namely planning, implementing, observing, and reflecting. This research was conducted in two cycles where each cycle was carried out in two meetings. The results showed that the learning completeness in the first cycle was 67.86%, increasing to 82.14%.